Chapter Per uno studio sulla ricezione di Boccaccio volgare: il Filostrato come modello compositivo del libro d'amore tra i secoli XV e XVI - Carnazzi, Francesca (Studi e saggi, 2022)
Between the 15th and 16th century, the main archetype of court poetry and its "codice lirico", represented by Petrarca in the Rerum Vulgarium Fragmenta, could be flanked by the model of the lyrical Boccaccio, whose vulgar love works, including Filostrato, seem to be alive in the memory of pre-Bembian writers because of the presence, for example, of stylistic features and themes typical of an "codice elegiaco".